2002
DOI: 10.5713/ajas.2002.79
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Necessity of Iron Injection to Newborn Piglets

Abstract: The growth and immune responses to endotoxin lipopolysaccharide (LPS) challenge (20 µg/kg) of piglets with and without a iron dextran injection (Fe, 200 mg/head) two days after birth are compared. Sixty-four newborn piglets from eight litters were allocated randomly to one of four treatments. The control received no iron dextran and only saline (Sal) injection on the second and fifteenth day after birth (Sal-Sal). The remaining three groups received Fe-Sal, Sal-LPS, Fe-LPS treatments respectively. On fifteen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In our previous iron deficiency study in piglets, ID piglets did become clinically anemic and showed impaired growth (Antonides et al, 2015b ). Our study results complement the findings of Yu et al ( 2002 ) that early-life iron deficiency that does not lead to anemia does not affect growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our previous iron deficiency study in piglets, ID piglets did become clinically anemic and showed impaired growth (Antonides et al, 2015b ). Our study results complement the findings of Yu et al ( 2002 ) that early-life iron deficiency that does not lead to anemia does not affect growth.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 2 suggests that control animals had slightly higher weights, yet this finding was not confirmed statistically. A study by Yu et al ( 2002 ) also showed no effects of an iron injection on growth performance in piglets. In their study, by offering creep feed, piglets did not become clinically anemic.…”
Section: Discussionmentioning
confidence: 95%
“…In their study, Lipiñski et al showed that by administrating iron to piglets in two doses at day 3 and 10 instead of in one dose, toxicity can be reduced and iron uptake is improved. Moreover, Yu et al ( 2002 ) argue that a 200 mg iron dextran injection does not contribute to overall performance of piglets at 15 days of age when creep feed is provided from day 7 onward, and consequently may not be a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the most common method of anaemia prevention is to inject 200 mg iron as iron dextran on the 3 rd day of life (Carlsson et al 1974;Yu et al 2002). The use of new genetic lines and changes in management techniques have raised concerns about the efficacy and safety of this method.…”
Section: Single Injectionmentioning
confidence: 99%